Sonographic assessment of the anatomy and common pathologies of clinically important bursae - Ivanoski, Slavcho; Vasilevska Nikodinovska, Violeta (Sciendo, 2019)
High-resolution ultrasonography has many advantages in the imaging of the musculoskeletal system, when compared to other imaging methods, particularly in superficial, easily accessible parts of the body. It is a perfect diagnostic tool for visualizing the most common pathologies of the musculoskeletal system, including the bursae. Inflammation of bursae is frequent, and it can mimic other diseases of the musculoskeletal system. Therefore, knowledge of normal ultrasound anatomy of the bursae, their exact location in the human body, and the sonographic signs of their most common pathologies is essential for establishing a quick and accurate diagnosis by ultrasound. Common conditions affecting bursae, leading to bursitis, include acute trauma, overuse syndromes, degenerative diseases, inflammatory conditions (rheumatoid arthritis, psoriatic arthritis, gout etc.), infections such as tuberculosis, synovial tumors and tumor-like conditions (pigmented villonodular synovitis, osteochondromatosis), and many more. This review article presents and explains ultrasound examples of the most frequent pathological conditions affecting bursae. Images include normal and pathological conditions of bursae around the shoulder joint, elbow, hip, knee, and ankle joint.
Keywords: high-resolution ultrasonography; bursa; anatomy; inflammation